Selection of hard coatings applied to industrial parts - Tabuchi Matsumoto, Edgardo (1999)
In any industrial operation, a major problem in the maintenance of tools, equipment and machinery is that of minimizing wear or recovering worn parts, the cost of which is less than the cost of changing them, for which it is important to recognize the problem and the way to recover them, which generally involves the application of a metallic coating by welding and machining for its finishing. But this is not everything, the most important thing is to know how and with what material to reprocess the piece; For this, it is necessary to know how to select the appropriate type of coating and its application process. The purpose of this work is to select the most suitable coating for the base metal of the worn part.